Non-Thermal Plasma Applications in Maize Seed Remediation, Disinfection, and Improvement for Growth: A Review - Diana Guadalupe Gutierrez-Leon; Jorge Jurado-Paramo; Benjamin Gonzalo Rodriguez-Mendez; Diego Medina-Castro; Regulo Lopez-Callejas (IEEE Access)
Maize is a crucial cereal with significant global importance due to its nutritional value and adaptability. However, its production is increasingly threatened by contamination—both chemical and microbiological—as well as climate change, which negatively impacts supply. Current alternatives aimed at ensuring production often come with considerable adverse effects. In this context, non-thermal plasma (NTP) emerges as a promising technology. It generates reactive chemical species and can also produce associated phenomena such as ultraviolet radiation emission and shock wave formation, which may help protect agricultural yields. Research over the past decade has consistently highlighted the potential of NTP to enhance the germination and development of maize seeds. This review is particularly relevant because it synthesizes current information and provides a structured perspective on the application of NTP in agriculture. It analyzes the experimental conditions—such as voltage, power, working gas, and treatment capacity—as well as the materials and typical discharge configurations in detail. This analysis is crucial for informing future research and refining these treatments. Furthermore, a significant contribution of this work is the categorization of scientific literature based on observed agronomic benefits into four key areas: chemical decontamination, inactivation of pathogenic microorganisms, improvement of seed physical properties, and optimization of seed storage conditions. This framework not only enhances understanding of the advances and multiple positive impacts of NTP but also emphasizes the importance of this technology for sustainable agriculture and food security. Additionally, it identifies knowledge gaps and promising areas for innovation.